Efektivitas Penerapan Model PjBL terintegrasi STEAM terhadap Keterampilan Proses Sains, Berpikir kreatif, dan Berpikir kritis pada Bidang Studi Biologi SMA - B, Nurhayati; Adnan, Adnan; Azis, Andi Asmawati; Ismail, Ismail; Hadis, Abdul; Suriyani, Suriyani; Isrul, Muhammad; Latif, Rahmawati (Jurnal Biotek, 2025)
Picking the wrong learning model can obstruct the growth of students' competencies. This research seeks to evaluate the efficacy of the Project-Based Learning (PjBL) model when integrated with the STEAM approach to boost science process skills, creative thinking, and critical thinking among high school students during biology lessons. Employing a quasi experiment with a quantitative method, the study included 65 tenth-grade students from SMA Negeri 9 Makassar, separated into an experimental group (PjBL-STEAM) and a control group (PjBL). Data collection utilized observation forms and written assessments, followed by analysis through N-Gain tests and inferential statistics. Findings indicated that the STEAM-combined PjBL model managed to enhance creative thinking abilities (N-Gain 0.52) and critical thinking (N-Gain 0.50) at a moderate level, although it fell short in sufficiently promoting science process skills, which remained in the good range. The study concludes that incorporating STEAM affects science process skills and creative